First‐Line Palliative HER2‐Targeted Therapy in HER2‐Positive Metastatic Breast Cancer Is Less Effective After Previous Adjuvant Trastuzumab‐Based Therapy. (August 2017) - Rier, Hánah N.; Levin, Mark‐David; van Rosmalen, Joost; Bos, Monique M. E. M.; Drooger, Jan C.; de Jong, Paul; Portielje, Johanneke E. A.; Elsten, Elisabeth M. P.; Ten Tije, Albert‐Jan; Sleijfer, Stefan; Jager, Agnes
Abstract: Background: Survival of patients with human epidermal growth receptor 2 (HER2)‐positive metastatic breast cancer (MBC) has improved dramatically since trastuzumab has become available, although the disease eventually progresses in most patients. This study investigates the outcome (overall survival [OS] and time to next treatment [TNT]) in MBC patients pretreated with trastuzumab in the adjuvant setting (TP‐group) compared with trastuzumab‐naïve patients (TN‐group) in order to investigate the possibility of trastuzumab resistance. Patients and Methods: Patients treated with first‐line HER2‐targeted‐containing chemotherapy were eligible for the study. A power analysis was performed to estimate the minimum size of the TP‐group. OS and TNT were estimated using Kaplan‐Meier curves and multivariable Cox proportional hazards models. Results: Between January 1, 2000, and June 1, 2014, 469 patients were included, of whom 82 were in the TP‐group and 387 were in the TN‐group. Median OS and TNT were significantly worse in the TP‐group compared with the TN‐group (17 vs. 30 months, adjusted hazard ratio [HR] 1.84 [1.15–2.96], p  = .01 and 7 vs. 13 months, adjusted HR 1.65 [1.06–2.58], p  = .03) after adjustment for age, year of diagnosis, disease‐free interval, hormone receptor status, metastatic site, and cytotoxic regimens. Conclusion: First‐line trastuzumab‐containing treatment regimens are less effective in patients with failure of adjuvant trastuzumab compared with trastuzumab‐naïve patients and might be due to trastuzumab resistance. The impact of trastuzumab resistance on the response on dual HER2 blockade with trastuzumab and pertuzumab and how resistance mechanisms can be used in the optimization of HER2‐targeted treatment lines need further investigation. Implications for Practice: Evidence on the efficacy of palliative trastuzumab‐based therapy after failure of trastuzumab in the adjuvant setting is limited because of a minority of patients treated with adjuvant trastuzumab in clinical trials. In this study, less clinical benefit of palliative trastuzumab‐based therapy was observed in patients relapsing after adjuvant trastuzumab compared with no adjuvant trastuzumab treatment. Subgroup analyses and multivariable analyses revealed that this was independent of possible confounding factors, including adjuvant taxane‐treatment. This might suggest a clinically meaningful impaired efficacy of trastuzumab after previous, in this case adjuvant, trastuzumab therapy. These results could have implications for treatment decision‐making after short progression‐free intervals on trastuzumab‐containing regimens in the palliative setting. Abstract : This retrospective study compares the efficacy of first‐line HER2‐targeted‐containing chemotherapy between patients who did or did not undergo adjuvant trastuzumab‐based treatment. Outcome in patients with metastatic breast cancer was investigated.